MACRO-MINERALS STATUS OF BUFFALOES IN RICE ZONE OF PUNJAB PROVINCE - T. N. Pasha; M. Z. Khan; U. Farooq; Y. A. Ditta; M. Ilyas; H. Ahmad (Journal of Animal and Plant Sciences, 2012)
A study was conducted to assess the macro-minerals status of buffalo on the basis of blood plasma, feedstuffs, soil and water analysis in Districts Hafizabad and Sheikhupura rice zone of Punjab province. Calcium (Ca), phosphorus (P), sodium (Na), potassium (K) and magnesium (Mg) status at different physiological stages (early lactation, mid-lactation, late lactation and dry) of buffaloes were determined. Lactating buffaloes were found significantly deficient in plasma Ca as compared to dry buffaloes. Plasma Ca, K and Na levels were significantly affected by physiological stages (P<0.05). Plasma Na and K levels were also affected by season (P<0.05). Lower plasma Na and sufficient K values were found in all physiological stages of buffalo. Sodium levels in water, soil and feedstuffs were lower than required. Higher level of K was found in roughages, soil and water. Higher levels of magnesium were found in soil. From these blood analysis. It was concluded that macro-mineral levels were significantly different (P<0.05) in blood plasma of different physiological stages of buffalo in these areas of Punjab and that animals needed minerals supplementation for health and economic benefits.
Keywords: Calcium ( Ca); phosphorus (P); sodium (Na); potassium ( K) and magnesium (Mg)